The role of communication technologies between choreographer and composer during Aotearoa/New Zealand's COVID-19 response. Issue Volume 21:Number 2(2021)Special Issue:Part 2 (21st December 2021) - Austin-Stewart, Jesse; Wright, Jason
Abstract : This article demonstrates how rapidly creatives can amend their creative processes to account for imposed limitations, particularly in the context of COVID-19. It documents a gradual shift in the way that in-person collaboration is valued. The use of communication technologies between composer and choreographer are compared through examples of the authors' own work both before and during the COVID-19 pandemic. This allows for observations to be made as to how interpersonal, domestic and international creative processes may develop in the future global 'new normal'. Aotearoa/New Zealand's current quasi-post-pandemic status allows for predictions to be made about what this collaborative relationship may look like for the rest of the world post-COVID.